Breast Fibroleiomysarcoma in Male. A Case Presentation - Lidia Torres Ajá; Julián Viera Llanes; Magalys Oliver (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
The first case of breast mixed carcinoma in male is presented and surgically operated in our university hospital ¨Dr. Gustavo Aldereguia Lima¨ in Cienfuegos, Cuba. It has been the first case in 27 years diagnosed to a 46 year old patient who lives in Cienfuegos city by means of a paraffin biopsy. It was performed in the pathologic anatomy department of our institution. The presentation of this case is considered of great scientific importance due to there is no other reference of a case like this before in our province or in any other of our country.